Indian College of Radiology and Imaging Guidelines on Interventions in Hepatocellular Carcinoma - Gupta, Pankaj; Kalra, Naveen; Chaluvashetty, Sreedhara B.; Gamangatti, Shivanand; Mukund, Amar; Abdul, Razik; Shyam, VS; Baijal, Sanjay Saran; Mohan, Chander (Indian Journal of Radiology and Imaging, 2022)
Hepatocellular carcinoma (HCC) is one of the most common malignancies and a significant cause of cancer-related death. Treatment of HCC depends on the stage of the tumor. As many patients with HCC are not deemed fit for surgical resection or liver transplantation, locoregional therapies play an essential role in the management. Image-guided locoregional treatments include percutaneous ablative therapies and endovascular therapies. The choice of an individual or a combination of therapies is guided by the tumor and patient characteristics. As the outcomes of image-guided locoregional treatments depend on the ability to achieve necrosis of the entire tumor along with a safety margin around it, it is mandatory to follow standard guidelines. In this manuscript, we discuss in detail the various aspects of image-guided locoregional therapies to guide interventional radiologists involved in the care of patients with HCC.
Keywords: hepatocellular carcinoma; interventional radiologists; locoregional treatment